CHRISTIAN COLONIZATION ON THE AMERICAN FRONTIER IN THE 1780s: THE COUNTESS OF HUNTINGDON'S PLAN AND THE AMERICAN RESPONSE. - Scott, John Thomas (Fides et historia, 2017)
The article discusses Christian colonization on the American frontier in the 1780s. Topics include Anglo-American interest in developing the Ohio River Valley in the 1740s, the 1783 Peace of Paris that ended the War of Independence for the Americans and transfered British claims on western lands to the U.S., and the factors that led Congress to dismiss the proposed colony.